The MBKM Programs in The Higher Education Settings:: EFL Students’ Expectations - Alamsyah, Kikin Feby; Karim, Sayit Abdul (UIBU, 2024)
The Merdeka Belajar Kampus Merdeka or Emancipated Learning-Independent Campus, hereinafter called MBKM, was launched by the Ministry of Education, Culture, Research, and Technology in 2020. In consequence, several higher education institutions may implement the MBKM curriculum. This study attempts to explore EFL students’ expectations towards eight programs of the MBKM. This study utilized qualitative descriptive, and the data were obtained through open-ended questions. Furthermore, 33 students in the sixth semester of the English Language Education Study Program (ELESP) participated as the respondents. The data were analyzed descriptively by describing the students’ expectations towards the MBKM programs in their study program. The findings revealed that they have high expectations for each program of MBKM, for instance, the Internship program provides a real-life experience, and clear job descriptions for students from different majors. The next program, the Teaching Assistance provides students opportunities to teach in the class and improve their teaching skills. Meanwhile, the Research activities enhance students’ critical thinking skills, problem-solving, article publication, and knowledge of research methods. Furthermore, the Humanity project enhances students’ social sensitivity to community issues. The Entrepreneur program facilitates students in the business sector and reduces unemployment in Indonesia. The Independent project enhances students’ innovative ideas and increases students’ bargaining power at both national and international levels. The last program, the Community service facilitates students to identify communities’ problems, and develop the village. The implication of the MBKM curriculum will positively contributed to the successful of the best practice of the aforementioned programs in each higher institution in the near future.